Development of a Land Resources Protection Model - KUZNETSOV, Evgeny Vladimirovich; SAFRONOVA, Tatyana Ivanovna; SOKOLOVA, Irina Vladimirovna; KHADZHIDI, Anna Evgen’evna; GUMBAROV, Anatoliy Dmitrievich (Journal of Environmental Management and Tourism; Vol 8 No 1 (2017): JEMT Volume VIII Issue 1(17) Spring 2017, 2017)
Effective and intensive development of agricultural industry is impossible without a system of measures to protect agricultural lands from different types of degradation. On the one hand, it is necessary to provide a maximum yield of agricultural crops and, on the other hand, to maintain and increase soil fertility, as well as to prevent negative human impact on the environment. More extensive soil fertility recovery requires a system of measures: application of fertilizers, agricultural and ameliorative practices, stimulation of humification and others. Humus is a key element of soil fertility. It accelerates biochemical and physiological processes, metabolism and total energy of processes in a plant body, intensifies nutrient enrichment, thus increasing the crop and its quality. Soil exhaustion due to humus reduction may result in a disaster for the agro industrial complex of a region. Soil fertility is the national heritage and the country’s strategic reserve. This article suggests that the problem should be solved by creating the Agro Landscape - Technology system and studying the responses of the simulated system on changes in its characteristics and initial conditions according to the considered methods of control over working operations. The methodology being designed provides practical methods of making forecasts and using them in solving management problems where many interrelated (system) factors and phenomena should be considered and vast forecast data should be used.